2021
DOI: 10.2478/czoto-2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health and Safety Management in Terms of Special Employee Needs – Case Study

Abstract: Every employer is responsible for ensuring safe and hygienic working conditions. According to the Labor Code and the relevant regulations, the elements of safe and hygienic working conditions in each enterprise are very similar. Differences arise when a specific industry or special psychophysical needs of an employee are taking into consideration. There is a specific group of employees for whom the working conditions organized by the employer in terms of occupational health and safety differ from the average w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Therefore, there is no problem adapting these conditions also to people with disabilities. Recently, it was observed that the activation of people with physical and intellectual disabilities [26] and their employment in various types of enterprises, including production should be assessed very positively.…”
Section: Human Factor In Sustainable Productionmentioning
confidence: 99%
“…Therefore, there is no problem adapting these conditions also to people with disabilities. Recently, it was observed that the activation of people with physical and intellectual disabilities [26] and their employment in various types of enterprises, including production should be assessed very positively.…”
Section: Human Factor In Sustainable Productionmentioning
confidence: 99%
“…Occupational health and safety management is an inseparable element of a comprehensive management system based on the quality criterion (Zymonik, et al, 2013). If the OHS system functions properly, it improves the economic performance of the enterprise, thanks to better than before management of processes in which OHS hazards may occur (Niciejewska and Kiriliuk, 2020;Niciejewska, 2021;Woźny, 2020). The aim of the study is to assess the importance of the factor related to work safety in selected enterprises from the heavy industry sector.…”
Section: Introductionmentioning
confidence: 99%